Arabidopsis Leaf Flatness Is Regulated by PPD2 and NINJA through Repression of CYCLIN D3 Genes. Issue 1 (10th July 2018) - Baekelandt, Alexandra; Pauwels, Laurens; Wang, Zhibiao; Li, Na; De Milde, Liesbeth; Natran, Annelore; Vermeersch, Mattias; Li, Yunhai; Goossens, Alain; Inzé, Dirk; Gonzalez, Nathalie
Abstract : Down-regulation of the PPD2/NINJA complex results in a convex-shaped primary cell cycle arrest front, upregulation of CYCD3 genes, and plants with dome-shaped leaves. Abstract: In Arabidopsis ( Arabidopsis thaliana ), reduced expression of the transcriptional regulator PEAPOD2 ( PPD2 ) results in propeller-like rosettes with enlarged and dome-shaped leaves. However, the molecular and cellular processes underlying this peculiar phenotype remain elusive. Here, we studied the interaction between PPD2 and NOVEL INTERACTOR OF JAZ (NINJA) and demonstrated that ninja loss-of-function plants produce rosettes with dome-shaped leaves similar to those of ppd mutants but without the increase in size. We showed that ninja mutants have a convex-shaped primary cell cycle arrest front, putatively leading to excessive cell division in the central leaf blade region. Furthermore, ppd and ninja mutants have a similar increase in the expression of CYCLIN D3;2 ( CYCD3;2 ), and ectopic overexpression of CYCD3;2 phenocopies the ppd and ninja rosette and leaf shape phenotypes without affecting the size. Our results reveal a pivotal contribution of NINJA in leaf development, in addition to its well-studied function in jasmonate signaling, and imply a new function for D3-type cyclins in, at least partially, uncoupling the size and shape phenotypes of ppd leaves.